Cartoon videos as a tool to enhance listening skills in fourth graders - Parraga Lino, Alisson Fernanda (2025)
Cartoon videos are an innovative and engaging tool for improving fourth graders' listening comprehension. By combining images and audio, they facilitate exposure to English in meaningful contexts, making learning more enjoyable and effective. This study analyzed the us of animated videos to reinforce the listening comprehension, considering the perceptions and experiences of English teachers working with students of this age. Using interviews as a qualitative method, it identified practical strategies, addressed possible challenges, and evaluat their impact on student motivation and participation. The results offered new insights into the us of creative strategies in learning English as a foreign language (EFL) and provided useful tool for improving listening comprehension in elementary school.